2023
DOI: 10.3390/jcm12083003
|View full text |Cite
|
Sign up to set email alerts
|

Connection between Cardiac Fibrosis Biomarkers and Echocardiography Parameters in Advanced Chronic Kidney Disease Patients

Abstract: Background: Myocardial fibrosis represents a mainstay pathway in the pathophysiology of uremic cardiomyopathy. This process leads to structural and functional changes in the heart, which can be detected by echocardiography. The purpose of our study was to determine the association between four echocardiographic parameters (ejection fraction (EF), global longitudinal strain (GLS), mean E/e’ ratio, and left atrial volume indexed) and biomarkers associated with cardiac fibrosis, such as procollagen type I carboxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
2
0
4
Order By: Relevance
“…In patients with chronic kidney disease, PICP was associated with left ventricular filling pressures and predicted cardiovascular death and all-cause mortality [69]. A recent study from our group proved that in patients with advanced chronic kidney disease, not yet on dialysis, PICP is associated with the value of global longitudinal strain, suggesting subclinical fibrosis [70].…”
Section: Collagen Biomarkersmentioning
confidence: 89%
“…In patients with chronic kidney disease, PICP was associated with left ventricular filling pressures and predicted cardiovascular death and all-cause mortality [69]. A recent study from our group proved that in patients with advanced chronic kidney disease, not yet on dialysis, PICP is associated with the value of global longitudinal strain, suggesting subclinical fibrosis [70].…”
Section: Collagen Biomarkersmentioning
confidence: 89%
“…Connective Tissue Growth Factor, CTGF), корин (син. предсердный натрийуретический пептид-превращаю щий фермент), секреторные продукты мезенхимных стромальных клеток и ряд маркеров воспаления [11]. Определение их уровней в крови используется для неинвазивной оценки фиброза миокарда [11,12], при этом в той или иной степени была подтверждена их клиническая значимость при различных сердечно-сосудистых заболеваниях и в общей популяции [13][14][15][16][17][18].…”
Section: аритмииunclassified
“…предсердный натрийуретический пептид-превращаю щий фермент), секреторные продукты мезенхимных стромальных клеток и ряд маркеров воспаления [11]. Определение их уровней в крови используется для неинвазивной оценки фиброза миокарда [11,12], при этом в той или иной степени была подтверждена их клиническая значимость при различных сердечно-сосудистых заболеваниях и в общей популяции [13][14][15][16][17][18]. Так, например, уровень галектина-3 в сыворотке крови ассоциирован с ремоделированием тканей сердца по данным экспериментальных исследований на лабораторных животных, однако для проверки полученных научных данных необходимы дальнейшие клинические исследования на людях [13].…”
Section: аритмииunclassified
See 1 more Smart Citation
“…In addition, specific fibrosis biomarkers such as procollagen type I carboxy-terminal propeptide (PICP), procollagen type III N-terminal peptide (P3NP), and galectin-3 (Gal-3) can be measured to assess paraclinical signs of myocardial fibrosis. The study of Ureche et al [ 3 ] aimed to investigate the relationship between four echocardiographic parameters (ejection fraction (EF), global longitudinal strain (GLS), mean E/e’ ratio, and left atrial volume index (LAVI)) and biomarkers associated with cardiac fibrosis, namely PICP, P3NP, and Gal-3, in patients with ESKD before initiating dialysis. This research revealed a robust correlation between PICP and all four echocardiographic parameters, suggesting that PICP could serve as a potential non-invasive indicator of myocardial fibrosis, impacting both systolic and diastolic dysfunction.…”
mentioning
confidence: 99%